Multiple Fourier sums and ψ-strong means of their deviations on the classes of ψ-differentiable functions of many variables - Lasuriya, R. A.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We present results concerning the approximation of ψ-differentiable functions of many variables by rectangular Fourier sums in uniform and integral metrics and establish estimates for φ-strong means of their deviations in terms of the best approximations.